Nighttime Hypoglycemia in Children with Type 1 Diabetes after one Day of Football Tournament - Kamiński, Mikołaj; Gawrecki, Andrzej; Araszkiewicz, Aleksandra; Szadkowska, Agnieszka; Skowrońska, Bogda; Stankiewicz, Witold; Michalak, Arkadiusz; Cieluch, Aleksandra; Dżygało, Katarzyna; Seget, Sebastian; Biegański, Grzegorz; Adamska, Anna; Ksiądz, Katarzyna; Szymańska-Garbacz, Elektra; Flotyńska, Justyna; Zozulinska-Ziolkiewicz, Dorota (International Journal of Sports Medicine, 2020)
The aim of the study was to investigate factors related to the occurrence of nighttime hypoglycemia after a football tournament in children with type 1 diabetes mellitus. The multicenter study (GoalDiab study) included 189 children and adolescents with type 1 diabetes mellitus, from 11 diabetes care centers in Poland. Hypoglycemia was defined according to the International Hypoglycemia Study Group Statement. We analyzed the data of 95 participants with completed protocols with regards to nighttime hypoglycemia (82% male), aged 11.6 (9.8–14.2) years, diabetes duration 5.0 (2.0–8.0) years. There were 47 episodes of nighttime Level 1 hypoglycemia (≤3.9 mmol/L). Occurrence of clinically important Level 2 hypoglycemia (<3.0 mmol/L) during a game period was positively associated with nighttime hypoglycemia (≤3.9 mmol/L) incident (Odds Ratio=10.7; 95% Confidence Interval: 1.1–100.2; p=0.04). Using Continuous Glucose Monitoring was negatively associated with the occurrence of nighttime hypoglycemia (≤3.9 mmol/L) compared with using glucose meters or Flash Glucose Monitoring (Odds Ratio=0.31; 95% Confidence Interval: 0.12–0.83; p=0.02). The occurrence of clinically important hypoglycemia related to physical activity is associated with the occurrence of hypoglycemia during the night. Continuous Glucose Monitoring is negatively associated with nighttime hypoglycemia after a day of competition.
Keywords: type 1 diabetes; exercise; nighttime hypoglycemia; football